Chattering reduction effect on power efficiency of ifoc based induction motor - Dedid Cahya Happyanto; Angga Wahyu Aditya (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Nowadays, the strategies to control Induction Motor (IM) is growing fast. The vector control strategies give better performance than the scalar control to control IM. IFOC is one of the vector control strategies which more realistic to apply in industry, military, and transportation. However, IFOC requires Sliding Mode Control (SMC) with the Lyapunov function to ensure robustness and stability. The first-order SMC or ordinary SMC uses boundary layers technique such as the saturation function and the tangent-hyperbolic function to overcome the chattering phenomenon. The performance of boundary layer is analyzed in rotor speed response, stator current response in dq0 frame and power performance. In rotor speed response, the SMC with and without boundary layer has error steady-state less than 2%. In stator current response with dq0 frame, the boundary layer with tangent-hyperbolic function has the best performance. The power analysis shows that the boundary layer with saturation function has an active power loss of 39.16%, reactive power loss of 23.37% and apparent power loss of 30.30%. The boundary layer with tangent-hyperbolic functions has the best performance in reducing power consumption with active power loss of 41.24%, reactive power loss of 24.78% and apparent power loss of 31.96%.